Modelling precipitation kinetics: Evaluation of the thermodynamics of nucleation and growth. (September 2015) - Rheingans, Bastian; Mittemeijer, Eric J.
Abstract: Modelling of (solid-state) precipitation kinetics in terms of particle nucleation and particle growth requires evaluation of the thermodynamic relations pertaining to these mechanisms, i.e. evaluation of the nucleation barrier and of the Gibbs–Thomson effect. In the present work, frequently occurring problems and misconceptions of the thermodynamic evaluation are identified and a practical approach with regard to kinetic modelling is proposed for combined and unified analysis of the thermodynamics of nucleation and growth, based on the fundamental thermodynamic equilibrium consideration in a particle–matrix system. A computationally efficient method for numerical determination of the thermodynamic relations is presented which allows an easy and flexible implementation into kinetic modelling. Abstract : Highlights: A thermodynamic evaluation method for modelling precipitation kinetics is proposed. Inconsistent thermodynamics of nucleation and growth are inherently excluded. Thermodynamic data can be efficiently incorporated into the kinetic model.